Methodological challenges in evidence gathering and assessment for guideline development in rare diseases: an example from hemophilia - Yeung, Cindy Hoi Ting (My University, 2016)
The guideline development process can be challenging when diseases are rare. The development of the NHF-McMaster Guideline on Care Models for Hemophilia Management presented an opportunity to identify methodological challenges for guideline development in rare diseases. Several methodological challenges were identified in the evidence gathering and assessment stages. Eight challenges were presented in the development of a systematic review on care models for hemophilia management. The barriers to conducting the systematic review were mostly due to the paucity of high quality evidence in hemophilia care models. Due to the paucity of high-quality evidence typical of a rare condition such as hemophilia, indirect evidence from other chronic conditions were sought through an overview of reviews. Seven challenges were identified in the development of an overview on integrated multidisciplinary care for the management of chronic conditions in adults. The barriers were mainly due to unestablished methodology for conducting overviews, and the challenge of applying this evidence in the context of hemophilia for the guideline. To overcome the methodological challenges with evidence gathering and assessment for rare disease guideline development, the decision-making process to derive solutions were transparently presented. Overall, the methodological challenges as well as apparent facilitators from a rare disease setting are shown to be related to the barriers and facilitators at the research, clinical, and guideline development phase. As a result, using an example from hemophilia, this thesis has demonstrated that it is possible to develop high quality guidelines for rare diseases.
Keywords: care models; delivery of health care; hemophilia; integrated care; guideline methodology; indirect evidence; chronic conditions; health care team